Assessing the socio-cognitive determinants of personal protective equipment uses among domestic waste collectors in the Ho municipality, Ghana: A cross-sectional study - Samuel Yaw Lissah; Martin Amogre Ayanore; John K. Krugu; Matilda Aberese-Ako; Robert A.C. Ruiter (PLoS ONE, 2025)
Domestic waste collectors (DWCs) are exposed to occupational safety and health related morbidities and mortalities globally due to the non-use, improper use, and non-availability of personal protective equipment (PPE) in their jobs which endangers DWCs’ lives, safety, and well-being. The present study investigated the extent to which socio-cognitive determinants predicted PPE use among DWCs in the Ho municipality in the Volta Region in Ghana. A quantitative cross-sectional survey was conducted among DWCs (n = 344) in the Ho Municipality of Ghana to assess the socio-cognitive determinants of PPE use. The questionnaire consisted of 107 items that were informed by a literature review in previous qualitative research, and two theoretical frameworks explaining behavior (i.e., the Health Belief Model (HBM) and Reasoned Action Approach (RAA) and measured constructs such as perceived severity and susceptibility of work-related health risks, perceived benefits, and barriers, perceived norm, and self-efficacy towards PPE use. Partial least squares structural equation modeling (PLS-SEM) was used to evaluate the structural model describing the relationship between the socio-cognitive determinants and intention to use PPE, which was the main outcome measure. The integrated model explained 67% of the variance in PPE-use intention. Intention to use PPE was significantly positively and directly influenced by attitude (β = 0.174, p < 0.001), indicated cues to action (β = 0.500, p < 0.001), perceived rule enforcement by the management (β = 0.114, p < 0.05), and self-efficacy (β = 0.199, p < 0.01). The direct effect of subjective norms on intention to use PPE was not significant (β = 0.040, p = 0.396). Attitude in turn was significantly predicted by perceived severity (β = 0.244, p < 0.001), perceived benefits (β = 0.209, p < 0.01), and behavioral beliefs (β = 0.342, p < 0.001), whereas perceived barriers were significantly associated with self-efficacy (β = 0.377, p < 0.001). In conclusion, the current study successfully expanded the utility of HBM and RAA in assessing the socio-cognitive determinants of PPE use among DWCs in a developing economy. Thus, the findings highlight the combined influence of individual beliefs and organizational enforcement on DWCs’ motivation to use PPE. Interventions should pair hazard‑communication and self‑efficacy training with strict managerial enforcement to strengthen PPE compliance.